Tracking immunodynamics by identification of S-G2/M-phase T cells in human peripheral blood. Issue 112 (August 2020) - Muñoz-Ruiz, Miguel; Pujol-Autonell, Irma; Rhys, Hefin; Long, Heather M.; Greco, Maria; Peakman, Mark; Tree, Tim; Hayday, Adrian C.; Di Rosa, Francesca
Abstract: The ready availability of human blood makes it the first choice for immuno-monitoring. However, this has been largely confined to static metrics, particularly resting T cell phenotypes. Conversely, dynamic assessments have mostly relied on cell stimulation in vitro which is subject to multiple variables. Here, immunodynamic insights from the peripheral blood are shown to be obtainable by applying a revised approach to cell-cycle analysis. Specifically, refined flow cytometric protocols were employed, assuring the reliable quantification of T cells in the S-G2 /M phases of the cell-cycle (collectively termed "T Double S" for T cells in S -phase in S anguine : in short "TDS " cells). Without protocol refinement, TDS could be either missed, as most of them layed out of the conventional lymphocyte gates, or confused with cell doublets artefactually displaying high DNA-content. To illustrate the nature of TDS cells, and their relationship to different immunodynamic scenarios, we examined them in healthy donors (HD); infectious mononucleosis (IM) patients versus asymptomatic EBV + carriers; and recently-diagnosed T1D patients. TDS were reproducibly more abundant among CD8 + T cells and a defined subset of T-regulatory CD4 + T cells, and were substantially increased in IM and a subset of T1D patients. Of note, islet antigen-reactive TDS cell frequencies were associated with an aggressive T cell effector phenotype, suggesting that peripheral blood can reflect immune events within tissues in T1D, and possibly in other organ-specific autoimmune diseases. Our results suggest that tracking TDS cells may provide a widely applicable means of gaining insight into ongoing immune response dynamics in a variety of settings, including tissue immunopathologies where the peripheral blood has often not been considered insightful. Highlights: "TDS " cells (i.e. in S-G2 /M phases of cell cycle) are present in peripheral blood. TDS cells are represented to different degrees in different T cell subtypes. TDS cells were associated with activated effector functions in T1D patients. TDS analyses can potentially functionally refine immuno-monitoring in many settings. Abstract.